PENGARUH SALESMANSHIP, KUALITAS HUBUNGAN dan NILAI KONSUMEN TERHADAP LOYALITAS KONSUMEN MEBEL PADA PT. MUSTIKA JATI JEPARA - Khoiruddin, Muhammad Afif; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2017)
This study aimed to analyze the influence of salesmanship, relationship quality, and consumer value on consumer loyalty and also to determine which variables are the dominant influence among three variables salesmanship, relationship quality, and consumer value on consumer loyalty.The population used in this research is the consumer who has ever bought furniture at PT.MUSTIKA JATI JEPARA, Jl. KH. Wahid Hasyim KM 2, Jepara. The samples are obtained by using purposive sampling method, that the sampling technique is based on certain characteristics, which is considered to have links with the characteristics of the population that has been determination before. Methods of data analysis using multiple linear regression analysis.The results showed that the variables of salesmanship, relationship quality and consumer value simultaneously significant effect on consumer loyalty. Then partially variable relationship quality has the highest significant effect on consumer loyalty, while the consumers value have influence with significance level to the second highest on consumer loyalty, and salesmanship has the lowest significant influence on consumer loyalty .